Transesterification of palm-based methyl ester and trimethylolpropane for trimethylolpropane esters production using microwave-assisted heating - Mohamad Aziz, Nur Atiqah (2021)
Malaysia being the second largest palm oil producer in the world, is currently promoting environmentally friendly or green products including palm oil-based lubricants. Biolubricants have shown good potential as an alternative to mineralbased lubricants and exhibit superior lubricating properties. Trimethylolpropane triester (TMPTE) is one of the synthetic base oils for biolubricants and can be derived from palm oil. TMPTE has good thermal and oxidative stability, density, viscosity index, and pour point, and wear properties. TMPTE has been produced using conventional thermal-heating transesterification process which consumes more energy due to a long production time. In this study, microwave heating has been chosen as an alternative synthesis method in the production of TMPTE as it is known to provide a more efficient heating. The processing parameters for the microwave reaction were temperature (90 – 150˚C), catalyst amount (0.2 – 1.0 wt.%), reaction time (3 – 25 minutes), molar ratio TMP-to-PME (1:3 – 1:4.5), and pressure (10 – 50 mbar). The highest composition of TMPTE produced by microwave heating was found to be 69 % (98 % of total esters) obtained only in 10 minutes, at 130°C, 10 mbar pressure, using 0.6 wt.% catalyst, and 1:4 molar ratio of TMP-to-PME. Furthermore, sample preheating to 130℃ for microwave-assisted significantly reduced to 3 minutes as compared to 30 to 40 minutes required with conventional heating. To understand the mechanism of the microwave-assisted transesterification between PME and TMP, kinetics study of the reaction was conducted at 110, 120, 130 and 140°C. The reaction kinetics was successfully modelled in MATLAB using the second-order reversible reaction, and the results correlated well with the experimental data. The fastest reaction rate for TMPTE production occurred at 130℃, with activation energies ranged from 17.0 -24.7 kcal/mol, clearly lower than the conventional method. When compared to conventional heating method the lower activation energy reflects an energy savings of 68.4 %. The distribution of electric fields in the microwave-assisted transesterification associated with the hotspots, temperature profile and power absorbed were simulated using COMSOL Multiphysics 4.2. As some part of the microwave was absorbed by the sample, the electric field and heating profile showed an alignment of intense heating at the top corner of the sample. The electric field and power absorbed by the sample were 1.92 x 104 V/m and 1.38 x 107 W/m3, respectively. Overall, microwave heating has been proven successful in accelerating the production of TMPTE.